2013
DOI: 10.1080/0092623x.2012.675020
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of Online Chat Groups for Women Completing a Psychological Intervention for Female Sexual Dysfunction

Abstract: Because of the embarrassment that can surround female sexual dysfunctions, online interventions offer an anonymous and private treatment alternative. Recently, an online cognitive-behavioral treatment for female sexual dysfunctions was evaluated. Although significant improvements were observed in sexual functioning, the treatment was primarily a behavioral intervention because of difficulties with engaging participants in cognitive therapy over e-mail. To address this limitation, the use of chat groups was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…When given the opportunity, participants shared their experiences about living with HIV and managing their medications with other participants, and provided emotional support. Outside the area of HIV, these results support those of a prior study of an online chat group intervention that found that women with sexual dysfunction used the online tool as a way to receive feedback from other women (Hucker & McCabe, 2012). Together, these and other studies (Fox, 2011) suggest that online peer-to-peer interactions are particularly useful for people living with an ongoing illness or condition to share strategies for overcoming barriers to managing their health, as well as gaining emotional support from each other.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…When given the opportunity, participants shared their experiences about living with HIV and managing their medications with other participants, and provided emotional support. Outside the area of HIV, these results support those of a prior study of an online chat group intervention that found that women with sexual dysfunction used the online tool as a way to receive feedback from other women (Hucker & McCabe, 2012). Together, these and other studies (Fox, 2011) suggest that online peer-to-peer interactions are particularly useful for people living with an ongoing illness or condition to share strategies for overcoming barriers to managing their health, as well as gaining emotional support from each other.…”
Section: Discussionsupporting
confidence: 83%
“…Although the use of online social networking websites is high among adults living in the United States (US) (Brenner & Smith, 2013), few technology-delivered sexual health interventions incorporate peer-to-peer features that may be an important source of support for clients. An exception to this, Huker and McCabe (2012) administered an online chat group intervention to 38 women with sexual dysfunction. Qualitative analysis showed that the online group chat intervention was acceptable and liked by most women and that it was helpful in addressing cognitive-affective aspects of the intervention.…”
mentioning
confidence: 99%
“…Revive significantly improved sexual functioning and relationship satisfaction vs a wait-list control group. 32 , 40 A second study assessing the program also found significant reduction in frequency of sexual difficulties and reduction in associated distress. 31 A subsequent program from the same research team, Pursuing Pleasure , was the first to combine Internet-based CBT, mindfulness training for FSD, and online chat groups.…”
Section: Introductionmentioning
confidence: 96%
“…32 Other studies were conducted in Australia, 33 the Netherlands 4 and Belgium. 3 The age of participants in the reviewed studies ranged from 18 to 82 years ( Table 1). Participants of the studies were female, 28,31 male, 33 both sexes 29,30 and couples.…”
Section: Study Characteristicsmentioning
confidence: 99%